(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
Energetics as a science of energy transformations studies how to exploit and apply various energy resources. In the economy, the energy sector is mostly characterized by the oligopolistic market system, whose competitiveness is the basic precondition for market liberalization. The focus of this research paper is on the Polish energy system, whose structure has changed significantly since the early 1990s. The biggest problem and threat to the Polish energy system is the huge import dependence on Russia, from which gas through the gas pipeline Yamal comes to Poland and also supplies the market of Western Europe. To reduce the dependence on Russian energy sources, the Swinoujscie LNG terminal was built, the largest Polish energy company PGNiG took over majority ownership over Yamal gas pipeline, and in the end Poland would import American gas into the LNG terminal. However, PGNiG, because of the lower cost, complements its energy market by Russian gas. Mutual ’games’ between the two largest energy companies, Polish PGNiG and Russian Gazprom, are presented through game theory. In the analysis, game theory finds optimal solutions and presents all available strategies. Two forms of game theory are presented: non-cooperative game in the form of a ‘prisoner’s dilemma’, and a cooperative game.